Long-term Trial of Corticosteroid Therapy for the Recurrence of Cerebral Amyloid Angiopathy-related Hemorrhages : A Case Study Using [11C] BF-227 Amyloid-PET - MACHIDA, Kazuko; IKEDA, Shu-ichi; YASUDE, Takuji (THE SHINSHU MEDICAL JOURNAL, 2014)
Aim : To clarify a long-term preventive effect of corticosteroid therapy for the recurrence of cerebral amyloid angiopathy (CAA)-related hemorrhages. Subjects and methods : Cases consisted of one male and two females, being consistent with the diagnosis of G3 to G4 in Boston validation criteria of CAA. To detect cerebral Aβ amyloidosis, they underwent positron emission tomography combined with a novel amyloid specific tracer, BF-227, all showing positive brain shadow. A 66-year-old man (case 1) with a diagnosis of G3 was given an initial dose of prednisolone at 50mg/day. The dose was gradually reduced and was tapered off 6 months later, but after the next 6 months cerebral hemorrhage recurred. He again received similar corticosteroid therapy. A 69-year-old woman (case 2) with a diagnosis of G3 was given dexamethasone 16mg/day after suffering recurrent cerebral hemorrhages. A week later dexamethasone was switched to prednisolone 30mg/day and the dose of this corticosteroid was gradually reduced, until being kept at 8mg/day. Another 75-year-old woman (case 3) with a diagnosis of G4 was given an initial dose of prednisolone at 30mg/day and the dose of this corticosteroid was gradually reduced and has been kept at 8mg/day. During the observation periods they were evaluated by clinical manifestations and T2* MR images : the total area of microbleeds was assessed by computer-assisted morphometry. After treatment two cases received a second PET scan and the regional standard uptake value ratio (SUVR) of BF-227 at the occipital lobe was compared with the previous one. Results : Case 1 suffered a small hemorrhage in the left frontal lobe at 20 months after receiving the corticosteroid therapy and steroid pulse therapy was added. During the remaining 33 months he has been free of cerebral hemorrhages. SUVR in his PET scan showed 2.0 to 2.2 in a 14- month follow-up period and the total area of microbleeds extended from 410.2 to 445.5mm2 during the 48-month observation period. Case 2 showed two simultaneous small hemorrhages at 29 months after starting the corticosteroid therapy and herdose of prednisolone was temporally increased. During the remaining 17 months she has not had any strokes and SUVR in her PET showed 1.5 to 1.4 in an 18-month follow-up period. The total area of microbleeds extended from 512.5 to 560.8mm2 during the 27-month observation period. Case 3 has been free of cerebral hemorrhages for 22 months after this corticosteroid therapy and the total area of microbleeds ranged from 152.5 to 154.1mm2 during the 13-month observation period. Conclusions : Corticosteroid therapy seems to be clinically effective for the long-term prevention of recurrences of CAA-related hemorrhages but current brain image data are inadequate to lead to this conclusion. This is the first report showing that domestically developed BF227 PET scan is useful in visualizing CAA lesions.